2011
DOI: 10.1111/j.1365-2036.2011.04770.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: non-bismuth quadruple (concomitant) therapy for eradication of Helicobater pylori

Abstract: Aliment Pharmacol Ther 2011; 34: 604–617 Summary Background  Traditional standard triple therapy for Helicobacter pylori infection (PPI‐clarithromycin‐amoxicillin) can easily be converted to non‐bismuth quadruple (concomitant) therapy by the addition of a nitroimidazole twice daily. Aim  To critically review evidence on the role of non‐bismuth quadruple therapy (PPI‐clarithromycin‐amoxicillin‐nitroimidazole) in the treatment of H. pylori infection. Methods  Bibliographical searches were performed in MEDLINE an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(114 citation statements)
references
References 109 publications
4
107
0
3
Order By: Relevance
“…Eradication rates for concomitant and sequential therapies were 100% vs 75% for clarithromycin-resistant strains and 75% vs 60% for clarithromycin-resistant/metronidazoleresistant strains [97] . A meta-analysis of 15 studies showed a mean H. pylori eradication rate of 90% by ITT analysis for concomitant therapy and reported that longer treatment improved the outcomes compared to STT [98] .…”
Section: Are There Suitable Sequential and Concomitant Therapy Alternmentioning
confidence: 99%
“…Eradication rates for concomitant and sequential therapies were 100% vs 75% for clarithromycin-resistant strains and 75% vs 60% for clarithromycin-resistant/metronidazoleresistant strains [97] . A meta-analysis of 15 studies showed a mean H. pylori eradication rate of 90% by ITT analysis for concomitant therapy and reported that longer treatment improved the outcomes compared to STT [98] .…”
Section: Are There Suitable Sequential and Concomitant Therapy Alternmentioning
confidence: 99%
“…Although three metaanalyses have concluded that quadruple therapy is equivalent to triple therapy, the basal studies pooled for these analyses used 7 day regimens and were conducted years ago when the rates of clarithromycin resistance were still low [10][11][12]. Unluckily, the difficulty to access some of the compounds used in this treatment (bismuth salts and tetracycline) in several countries, and until the new single capsule formulation is available worldwide [13], forces us to seek for non-bismuth-based alternatives [14,15].…”
Section: Editorialmentioning
confidence: 98%
“…Numerous treatment strategies containing a proton pump inhibitor and combination of two or more antibiotics such as clarithromycin (CLA), amoxicillin (AMX) and metronidazole (MTZ) or tetracycline (TET) have been successfully used to eradicate HP infection (Nagahara et al 2000;Chaabane & Al-Adhba 2015). Although the efficacy of such strategies in the therapy, the increasing use of antibiotics has led to the problem of drug-resistant strains (Essa et al 2009;Gisbert & Calvet 2011). Resistance rates have been reported vary from 0 to 45% for CLA, from 0 to 33% for AMX, from 10% to 90% for MTZ, from 6% to 21% for levofloxacin and from 5% to 59% for TET (Karamanolis et al 2014;O'Connor et al 2014;Song et al 2014).…”
Section: Introductionmentioning
confidence: 99%